Levetiracetam for Pediatric Posttraumatic Seizure Prophylaxis - Dragos A. Nita; Cecil D. Hahn (Pediatric Neurology Briefs Publishers, 2016)
Investigators from Nationwide Children's Hospital performed an observational cohort study of early post-traumatic seizures (EPTS) among 34 children with moderate to severe traumatic brain injury (TBI) who received levetiracetam (LEV) prophylaxis following admission to their pediatric intensive care unit.